FACTORS ASSOCIATED WITH HEPATITIS B AND C CO-INFECTION AMONG PEOPLE LIVING WITH HUMAN IMMUNODEFICIENCY VIRUS IN VIETNAM - Le Hieu Thuy Anh; Suchada Thaweesit (Belitung Raya Foundation, Indonesia, 2019)
Background: Human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV) are the leading causes of death from infectious diseases. Because of sharing same transmission routes, the co-infection of HIV with HBV or HCV is common. And the co-infections make HIV infected persons have higher morbidity and mortality than those who infected only with HIV. This study aims to investigate factors that may have influence on the co-infections of HBV or HCV among HIV positive individuals. Objective: The goals of this study were to identify factors associated with the co-infection of HBV or HCV among people living with HIV. Methods: Quantitative research method was applied in this study to examine factors associated with HBV or HCV co-infection among HIV infected people. A total of 250 HIV infected individuals in Khanh Hoa province, Vietnam were the sample of this study. It employed the Social Ecological Model (SEM) as a theoretical perspective that focused on multiple levels of factors. Descriptive statistic was used to describe the general characteristics of the respondents. And Binary logistic regression was carried out to measure the influence of factors on the co-infection. Results: The multivariate analysis of this study showed that HIV-HBV co-infection was associated significantly with residents of Nha Trang (OR= 7.179). Regarding HIV-HCV co-infection, being men (OR= 7.617), unemployed (OR= 4.013), a resident of Nha Trang (OR=10.894) and an injecting drug user (OR= 16.688) were risk factors of the co-infection. Conclusions: This study recommended that intervention strategies to prevent HIV-positive individuals from co-infection with either HBV or HCV should focus on altering individuals’ risk behaviors and their socio-economic environments. Also, specific preventing programs should be implemented and focus on unemployed populations, injecting drug users, men in general, as well as people living in particular areas, especially cities having a large number of people living with HIV.